2018
DOI: 10.1080/19390211.2018.1472711
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Curcumin on Serum Copper and Zinc and Zn/Cu Ratio in Individuals with Metabolic Syndrome: A Double-Blind Clinical Trial

Abstract: Metabolic syndrome is a complex disorder with high socioeconomic costs and a high global prevalence. The serum concentrations of some trace elements are higher in people with metabolic syndrome compared to normal individuals. Curcumin is derived from turmeric and has antioxidant and anti-inflammatory properties. Curcumin may therefore have a potential role in the management of cardiovascular risk. The aim of this study was to investigate the effects of curcumin on serum copper (Cu), zinc (Zn), and Zn/Cu ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…564 Another study showed that curcumin (1 g/day) and phospholipidated curcumin (1 g/day) supplementation for 6 weeks improved serum zinc levels in 120 patients with MetS. 565 In another study, nanocurcumin alone or in combination with aerobic exercise reduced serum levels of IL-6, MDA, and hs-CRP and increased IL-10, BDNF, and TAC in patients with MetS. 566 Nanocurcumin 80 mg/day for 12 weeks was also shown to reduce triglyceride levels and HOMA-β in patients with MetS.…”
Section: Turmeric and Curcumin In Inheritedmentioning
confidence: 99%
“…564 Another study showed that curcumin (1 g/day) and phospholipidated curcumin (1 g/day) supplementation for 6 weeks improved serum zinc levels in 120 patients with MetS. 565 In another study, nanocurcumin alone or in combination with aerobic exercise reduced serum levels of IL-6, MDA, and hs-CRP and increased IL-10, BDNF, and TAC in patients with MetS. 566 Nanocurcumin 80 mg/day for 12 weeks was also shown to reduce triglyceride levels and HOMA-β in patients with MetS.…”
Section: Turmeric and Curcumin In Inheritedmentioning
confidence: 99%
“…Similarly, the anti-obesity activity of curcumin is attributed to anti-inflammatory responses, oxidative stress balance, and endogenous antioxidant enzyme expression [ 66 ]. Safarian et al [ 67 ] reported that the ingestion of curcumin (1 g/day) and phospholipidated curcumin complex for six weeks increased the serum zinc and zinc-to-copper ratio, which represent two important antioxidants in patients with metabolic syndrome.…”
Section: Curcumin: a Bioactive Molecule With Potential For Edible Bio...mentioning
confidence: 99%
“…Some recent studies reported the effects of curcumin and its derivatives on some oxidative stress markers in MS patients ( 122 ), for instance, serum copper, zinc, and trace elements are elevated in patients with MS compared to healthy subjects ( 120 ). A double-blind clinical trial of 120 subjects with MS reported increased serum zinc and Zn/Cu ratio after administration of curcumin and phospholipid curcumin complex at a dose of 1 g/day for 6 weeks ( 123 ). However, Mohammadi et al reported no significant difference in the alteration of HSP 27 serum concentrations among the study groups (group received curcumin, phospholipid -curcumin complex, or a placebo for 6 weeks) ( 124 ).…”
Section: Other Clinical Studiesmentioning
confidence: 99%